Study of technical specifications for non-API 140 casing in ultra-deep well. (March 2019) - Wang, Jiandong; Kuanhai, Deng; Zhiping, Yin; Bing, Liu; Lin, Yuanhua; Feng, Yaorong
Abstract: In Tarim oilfield of China, the true vertical depth (TVD) is >6000 m, non-API 140 casings are often used as the intermediate and production casing. No industry standard has been established for such high grade casing, although there are some obvious shortcomings, such as sensitivity to defects and service environment, so that the fracture failure accidents of non-API 140 casing in Tarim oilfield happens frequently. Hence, this paper presents a discussion on the technical specifications of non-API 140 casing. Firstly, the system test and analysis of physical and chemical performance of non-API 140 casing material from various manufacturers have been conducted, including chemical composition, tensile properties, impact toughness, hardness, metallographic structure. Secondly, the analysis method of required minimum transverse impact toughness (CVNmin ) to resist cracking for pipe body and coupling of non-API casing has been presented, by which the effects of effective thickness and non-destructive examination level (defect depth) on CVNmin to resist cracking of pipe body and coupling under diffenrent internal pressure have been analyzed.Thirdly, the full-scale ductile burst test of non-API 140 casing has been performed based on API 5CT standard. Finally, based on experimental data and analysis, the technical specifications for non-API 140 casing are proposed. Cases Analysis of Tarim field shows no fracture failure occurs during the subsequent service after adopting those technical specifications. Highlights: Physical/chemical performance of non-API 140 casing from three manufacturers is obtained. Analysis method of required impact toughness to resist cracking has been presented. Full-scale ductile burst test of non-API 140 casing has been performed. Technical specifications for application of non-API 140 casing are proposed.